PERCEPTIONS OF FAMILY HEALTH TEAMS ON CONTRACEPTION CARE - Luciana Cristina dos Santos Maus; Evangelia Kotzias Atherino dos Santos; Marli Terezinha Stein Backes; Alcira Escobar Marín (Universidade Federal do Paraná, 2020)
Objective: To identify the perceptions of Family Health teams on contraceptive care. Method: A qualitative research, of the exploratory-descriptive type. Data collection was conducted by means of semi-structured interviews, totaling 55 participants active in the Family Health Strategy in a capital of southern Brazil. For the organization and coding of the data, the resources of the webQDA software were used and, for data analysis, the four generic processes were followed: apprehension, synthesis, theorization, and transfer. Results: Four categories emerged, namely: perceptions on contraceptive care; contraceptive care actions; characteristics of the people who demand contraceptive care; and sensations experienced by the teams when working in contraceptive care. Conclusion: The arguments and counterarguments raised by the participants need to be widely discussed during the work process of the teams, with the aim to improve contraception care, thus contributing to the reduction of unplanned pregnancies and their implications.